Response of selected hormonal markers during training cycles on indian female swimmers - Majumdar, P.; Srividhya, S.; Mandal, M.; Kalinski, M. I. (Biology of Sport, 2010)
The present study was taken up to monitor the fluctuations of the hormones testosterone, cortisol and T/C (Testosterone/Cortisol) ratio concentrations during the three phases of training namely preparatory phase, pre-competitive phase and competitive phase in Indian female swimmers. Blood samples were collected at the completion of each phase to study the impact of training on these hormones. Our results reveal that the testosterone and T/C ratio significantly decreases whereas cortisol increases in the subsequent periodised cycle and it was due to the intensity and volume of training. Our study concludes that the intensity and volume of training has effects on these hormones and also, a swimmer with higher testosterone, lowest cortisol and highest T/C ratio has the highest percentage difference of performance record between the preparatory and competitive phase. Hence, monitoring of these hormones is essential to avoid overtraining and to enhance the performance of the swimmers.